2012
DOI: 10.1097/sle.0b013e31825078f2
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Treatment of Gastric Gastrointestinal Stromal Tumors

Abstract: Laparoscopic surgery for gastric GIST is safe and feasible, even in large (>5 cm) tumors. Because endoscopic resection showed good results without recurrence, this approach can be useful in selected cases with a high operative risk or a need for preservation of organ function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 25 publications
0
46
0
Order By: Relevance
“…11 If GISTs are located in duodenum, more extensive resection, such as pyloruspreserving pancreaticoduodenectomy (PPPD), might be necessary due to anatomical features. 12,13 Recently, endoscopic resection including endoscopic mucosal resection (EMR) or endoscopic submucosal dissection (ESD) has been established as a standard therapeutic M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT method for differentiated intramucosal early gastric cancer (EGC) or even submucosal EGC confined to SM1 layer or ulcerative lesion < 3.0 cm in size, in the absence of lymphovascular invasion.…”
Section: Introductionmentioning
confidence: 99%
“…11 If GISTs are located in duodenum, more extensive resection, such as pyloruspreserving pancreaticoduodenectomy (PPPD), might be necessary due to anatomical features. 12,13 Recently, endoscopic resection including endoscopic mucosal resection (EMR) or endoscopic submucosal dissection (ESD) has been established as a standard therapeutic M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT method for differentiated intramucosal early gastric cancer (EGC) or even submucosal EGC confined to SM1 layer or ulcerative lesion < 3.0 cm in size, in the absence of lymphovascular invasion.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that endoscopic resection is safe and viable for patients with GISTs, even in tumors up to 5 cm in size [18]. In theory, endoscopic resection is a simple and feasible treatment for some tumors, but the risk of early tumor recurrence with incomplete resection is a major concern for the surgeon.…”
Section: Introductionmentioning
confidence: 99%
“…Lipoma or lymphangioma sometimes can be inferred based on the exposed tissue after biopsy. According to studies on SMTs with the likelihood of malignancy, malignancy was observed in 3.7% of GISTs smaller than 2 cm [6], and metastasis was observed in 2% of carcinoids smaller than 1 cm [7]. For this reason, recent guidelines recommend histological diagnosis for SMTs larger than 2 cm (United States and Europe) or 1 cm (Japan).…”
Section: Diagnosis Of Esophageal Smtmentioning
confidence: 99%